Modeling and Analyzing the Minimum Supercooling Temperature for a Novel I‐Type Thermoelectric Cooling With Various Pulse Currents - Tianzhen Yang; Bohong Lai; Junhong Hao; Kaicheng Liu; Zhenlan Dou; Xiaoze Du; Hongkun Lv (Energy Science & Engineering)
ABSTRACT Continuous improvement of transient supercooling effects in thermoelectric cooling is important for solving thermal management problems such as chip hot spots. In this paper, a new I‐type thermoelectric cooling structure is investigated, and its transient cooling performance is deeply investigated by a simulation method with the minimum cold end temperature as the index. We systematically analyze the cooling performance difference between the I‐type structure and the conventional π‐type structure under various pulse currents, and investigate the effects of structural parameters (such as the length of the thermoelectric legs and copper thickness) and current amplification on the minimum cold end temperature of the I‐type structure. The results show that, within a certain range, the decrease of copper thickness and the increase of the length of the thermoelectric legs are conducive to the reduction of the minimum cold end temperature, and the cooling performance of the I‐type structure is better than that of the π‐type structure under various pulse currents, especially when the current amplification factor is 20, the cold end temperature of the new structure is nearly 30 K lower than that of the conventional structure. The research demonstrates that the innovative design enhances the transient cooling efficiency, with the minimum cold end temperature serving as a definitive metric. This new structure not only exhibits a lower cold end temperature but also experiences a slower temperature increase as the pulse current diminishes. This study provides theoretical support for the application of thermoelectric cooling technology in the fields of high‐power cooling and high‐speed cooling.